Ethical Food Entrepreneurship (EFE) - Erasmus+ Project: Food for People – Planet – Profit - Ramalhosa, Elsa (2022)
The food industry is a complex, collective of diverse businesses that supply our food in the context of great environmental challenge. The world’s growing food demand and the need for ethical and sustainable practices have become a challenge that the EU and the UN are encouraging us all to tackle. The food and drink industry is the EU's biggest manufacturing sector in terms of jobs and value-added. The industry is dominated by SMEs; however, self-employment in the EU has not risen in decades. Potential entrepreneurs and SMEs have been slow to respond - because they lack professional capacity or skills to innovate/orchestrate change in business development, production and marketing of ethical food. We want to initiate a change in this regard with EFE and encourage/promote potential entrepreneurs to take that leap with support and knowledge.The main objective of the present work is to present the Ethical Food Entrepreneurship (EFE) Project, an Erasmus+ Projec